Management of pain in rheumatic diseases - Neha Goyal; Mohit Goyal; Vinod Ravindran (Indian Journal of Rheumatology)
Pain is often the presenting symptom of many rheumatic diseases, the predominant disabling symptom, the reason for frequent visits to the physician and a major cause of medical absenteeism, loss of work hours, and financial burden on the society. Pain in rheumatic diseases is now understood to be a result of interplay of inflammation, tissue damage, and neurogenic responses. Besides control of inflammation, the structural changes, central sensitization, and the associated issues of disturbances of sleep, mood, and cognition also need to be addressed. Apart from the useful addition of neuromodulators to our traditional repertoire of pain medications consisting of analgesics, nonsteroidal anti-inflammatory drugs, steroids, and opioids, there is a place for interventions in situations where pain persists even after reasonable control of widespread inflammation. These interventions are mostly percutaneous and have found applications in inflammatory, structural, as well as neurogenic pain. Interventional spine procedures, platelet-rich plasma therapy, ozone therapy, and radiofrequency ablation of neural structures have added new dimensions to the management of pain.